PENERAPAN MANAJEMEN DAN REKAYASA LALU LINTAS DI PERSIMPANGAN KECAMATAN TAMAN SIDOARJO DALAM UPAYA INTEGRASI TRANSPORTASI - Susanti, Anita; Linda, Ovilia; Hidayati, Ninik Wahju (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Intersection in Sidoarjo amount of traffic that has more than 5000 vehiclesper day that is the intersection Ngelom Rolak, Satria Ngelom intersection, and the intersection of New Marketpark. At the third intersection has the same condition, namely eksisiting trade area, with side barriers high. Metode used is survey research in the third intersection counting for 8.For the field survey is intersection Ngelom Rolak DS value of 1.55. For the intersection andt he intersection Ngelom Satria 1.530.68 Market New Garden. Alternatives are used to manufacture the intersection Ngelom Rolak is one-way street that is a new bridge for vehicles towards the old bridge to Surabaya and Sidoarjo direction, as well as widening the road. For Ngelom intersection Satria and New Market Parkalsomadeone-way street, so as to create a good integration.